Analisis Postur Kerja Menggunakan Metode REBA dan Kuesioner NBM Pada Operator Mesin Sizing SA-80 N1 di Industri Otomotif - Yohanes, Ricky; Al-Muqaffa, Figar Wafiq; Kusnadi, Kusnadi (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This research was conducted at a company engaged in automotive manufacturing which produces motorbikes and related spare parts. Based on the results of observations on the production process, especially the sizing process, it is still done manually and has the potential for musculoskeletal disorders. This research is an observational study with a cross-sectional design that focuses on Ergonomics and OSH (Occupational Health and Safety) studies. Data obtained by using the Nordic Body Map (NBW) questionnaire as a tool to measure workers' pain at or after work and using the Rapid Entire Body Assessment (REBA) method to analyze work posture. After completing the NBW questionnaire on 4 sizing machine operators, 1 operator with the highest total individual score of 46 was included in the low category and was then selected to calculate work posture using the REBA method. Based on the results of calculating work posture using the REBA method, the final REBA score is 8. This score indicates (action level) 4 with high-risk conditions and further investigation is needed to prevent Musculoskeletal Disorders (MSDs) in operators Keywords: Ergonomics, MSDs, NBM, REBA, Work Posture.